ON THE NEED TO INCREASE THE RELIABILITY OF LINEAR INSULATORS FOR DISTRIBUTION NETWORKS 10-20 KV - Yu. N. Shumilov (National Technical University "Kharkiv Polytechnic Institute", 2018)
Introduction. In Ukraine high voltage overhead distribution lines (OL) of class 6 and 10 kV are the most extended. Their total length exceeds 280,000 km. More than 95% of the lines are made on line supports from reinforced concrete racks. On all poles of the overhead line, pin insulators are installed. According to the data of operation experience, up to 60-70% of single-phase earth (SPE) faults due to «insulation» occurs on VL supports due to damage to line pin insulators, mainly during the thunderstorm period. Problem. Insufficient reliability of pin insulators leads to interruptions in power supply, accidents on the line, accidents in the area of reinforced concrete poles, where in the case of insulator damages, a long process of SPE occurs. Goal. The purpose of the work is to select the design and develop requirements for new linear insulators of 10-20 kV overhead lines that provide high resistance to lightning overvoltages with direct and inductive effects of lightning. Methodology. The research methodology consists in analyzing operational experience, calculating insulator parameters and laboratory tests. Results. Using statistical data on lightning parameters and data on mechanical loads on insulators, the main dimensions of line post insulators have been determined that will ensure their reliable operation under conditions of intense thunderstorm activity and extreme ice and wind loads. Conclusions. The main technical requirements for line post insulators for 10-20 kV distribution lines were formulated. On the 10 kV OL located in areas with increased thunderstorm activity it is recommended to use line post insulators instead of pin-type ones. On the OL-20 kV it is recommended to use only line post insulators. The use of high-lightning-resistant line post insulators on OL-10-20 kV will significantly increase the electrical safety and reliability of power supply to consumers. Increased by 2-3 times the cost of line post insulators in comparison with those used will be compensated for by the effects of reducing the number of collapsible supports, damage from under-supply of electricity, labor costs during transportation and restoration of destroyed supports, the moral side of reducing accidents in case of electric shock in the emergency zone. The insulators offered for OL-10-20 kV can be used for fixing both bare and protected wires. The exclusion from the design of the weakest elements – polyethylene caps and metal pins will increase the reliability of the power isolation unit.